Organizational commitment among academicians : its relationship with stress level and stress level coping strategies - Ashari, Hapriza; Ungku Ahmad, Ungku Norulkamar; Md. Noor, Suhaini; Abdul Rahman, Siti Aisyah (Faculty of Management and Human Resource Development, 2005)
Human resource is the most important asset in an organization. Nonetheless, the existence of stress in the workplace will reduce employees’ contributions to the organization. This is because, employees under stress usually have poor performance, more likely to be absent from the workplace, more prone to having accident in the workplace and have higher level of work dissatisfaction. In addition, lack of employees commitment towards the organization may also affect the organization’s performance. Nevertheless, not much study has been conducted to examine the relationship between employee’s commitment towards their organization and occupational stress. The aim of this study is to investigate the relationship between organizational commitment and occupational stress among the academic staff of Universiti Teknologi Malaysia (UTM), Skudai, Johor. In addition to that, the objectives of this study include identifying the stress factor that most influence commitment, the difference of stress level based on demography, the difference of commitment level based on demography as well as identifying the coping strategies adopted by the respondents. Correlation method, Stepwise regression analysis and Kruskal Wallis test were utilized in analyzing the data. The results show that majority of the UTM academic staff experience low level of stress and are moderately committed to the organization. Furthermore, this study also confirms that there exist negative significant relationship between stress and commitment. The results also show that the stress factors that most influence commitment are role ambiguity and role conflict. However, the influence of these stress factors on the academic staff’s commitment is only 27.7%. As for the difference of stress level based on demographic factors, it is found that there exists a significant difference among all the four demographic factors (sex, position, level of education and length of service). Nevertheless, only level of education shows that there is significant difference of the level of commitment. It is also found that most respondents utilize more than one type of coping strategies when dealing with stress.